The preparation of magnesium ferrous sulfate from pre-oxidized acid mine drainage - TAN Dongdong; NIE Guanghua; DENG Qiang (Gongye shui chuli)
The pre-oxidation acid mine drainage(AMD) generated during mining process exhibits a certain degree of acidity and contains a large amount of metal ions and sulfates. Traditional lime neutralization methods not only contribute to environmental pollution, but also cause resource wastage. This study employed a process involving nanofiltration, reduction, vacuum concentration, and crystallization to treat pre-oxidation AMD and produced magnesium ferrous sulfate crystals. The retention rate of different metal ions during nanofiltration was investigated, and the influence of Fe3+ reduction during the preparation process of magnesium ferrous sulfate were explored, along with the impact of crystallization conditions on crystal purity and yield. The results showed that the retention rate of nanofiltration for all metal ions reached over 93%, and the retention rate for iron and magnesium reached 98%. The optimal Fe3+ reduction effect occurred at pH of 1.0, temperature of 35 ℃, and reaction time of 40 minutes. When the concentration ratio of the mother liquor was 1∶2, the crystallization temperature was 35 ℃, and the stirring rate was 240 r/min, the recovery rates of iron and magnesium in mother liquor were 31.31% and 13.48%, respectively, and the purity of the product could reach more than 98%. Structural analysis of the crystals confirmed that the product was magnesium ferrous sulfate. Compared with the traditional lime neutralization method, this combination process could not only achieve pre-oxidation AMD treatment, but also realize resource recovery of ferrous magnesium sulfate.